2016
DOI: 10.1038/srep22123
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects and Mechanisms of Electroacupuncture at Ipsilateral or Contralateral ST36–ST37 Acupoints on CFA-induced Inflammatory Pain

Abstract: Transient receptor potential vanilloid 1 (TRPV1) and associated signaling pathways have been reported to be increased in inflammatory pain signaling. There are accumulating evidences surrounding the therapeutic effect of electroacupuncture (EA). EA can reliably attenuate the increase of TRPV1 in mouse inflammatory pain models with unclear signaling mechanisms. Moreover, the difference in the clinical therapeutic effects between using the contralateral and ipsilateral acupoints has been rarely studied. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 58 publications
1
61
1
Order By: Relevance
“…Based on results of our previous studies 4 , it was suggested that a total of 10 mice in each group is the minimum number necessary to perform the experiments. All experiments were performed in our laboratory during daylight hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on results of our previous studies 4 , it was suggested that a total of 10 mice in each group is the minimum number necessary to perform the experiments. All experiments were performed in our laboratory during daylight hours.…”
Section: Methodsmentioning
confidence: 99%
“…Electroacupuncture (EA) is a promising alternative to such drugs and has recently attracted much attention due to increasing evidence of its analgesic effects 2 , 3 . Previous studies using animal models have demonstrated the therapeutic effects of EA against inflammatory pain via neuronal and non-neuronal pathways, namely suppression of the transient receptor potential cation channel subfamily V member 1 (TRPV1) pathway 4 , generation of anti-nociceptive adenosine on adenosine A1 receptors (A1R) for local acupoints 5 7 , and stimulation of endogenous opioid secretion via the anesthesia pain descending pathway in the central nervous system 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were anesthetized with 1% isoflurane and given a single injection of 20 μ l saline (pH 7.4, buffered with 20 mM HEPES) or CFA (75% in saline, 0.5 mg/ml heat-killed M. tuberculosis [Sigma, St. Louis, MO]) in the plantar surface of the hind paw to induce chronic intraplantar inflammation [ 19 ]. Behaviour tests are conducted every 3 days after induction of chronic inflammatory pain.…”
Section: Methodsmentioning
confidence: 99%
“…The NR1, NR2A, NR2B, and NR2D subunits are distributed in the DRG and SC [19,20]. Activation of NRs can induce the influx of Ca 2+ and then lead to the activation of Ca 2+ /calmodulin-dependent protein kinase 2 (CaMKII) for signaling in the postsynaptic density [21]. There are four isomers of CaMKII in mammals, i.e., α, β, γ, and δ. CaMKII is a holoenzyme and a serine/threonine kinase that is highly expressed in the brain mainly participates in its phosphorylation [22].…”
Section: Introductionmentioning
confidence: 99%